IMPROVING THE EXISTING INFORMATION FACILITY IN SPECIAL LIBRARIES IN VISAKHAPATNAM USING A MARKETING APPROACH - Sasikala, C.; Patnaik, K. Rama (Malaysian Journal of Library and Information Science, 1999)
The study examines the marketing practices of three special libraries of Visakhapatnam City, Andhra Pradesh, India. This survey gathers data from library professionals and users, covering various aspects of their libraries. It is observed that some aspects of marketing strategies are used. Users also showed interest in obtaining value-added information services and expressed their willingness to pay for such services if necessary. The findings of the survey revealed the relevance and importance of marketing practices in non-profit organisations such as libraries and information centres.